Cover Feature: Potential Precursor Alternatives to the Pyrophoric Trimethylaluminium for the Atomic Layer Deposition of Aluminium Oxide (Chem. Eur. J. 31/2019). Issue 31 (26th April 2019) - Mai, Lukas; Boysen, Nils; Zanders, David; de los Arcos, Teresa; Mitschker, Felix; Mallick, Bert; Grundmeier, Guido; Awakowicz, Peter; Devi, Anjana
Abstract : Trimethyl aluminium alternative : In a bid to find an alternative to the hazardous, pyrophoric industrially used atomic layer deposition (ALD) precursor for Al2 O3, namely trimethyl aluminium (TMA), an intramolecular stabilising ligand system that yielded a new, promising, and non‐pyrophoric class of Al precursors was devised. Taming the igneous temperament of aluminium alkyls, the successful implementation of the new Al complexes in both thermal and plasma ALD sets up a safe alternative to TMA as the Al2 O3 thin films were of high quality, matching the standards obtained by the classical TMA process. More information can be found in the Full Paper by A. Devi et al. onpage 7489 .